EDUKASI MANAJEMEN USAHA PRODUK PANGAN LOKAL BERBASIS DAUN KELOR PADA MAJELIS TAKLIM KELURAHAN BUKIT WOLIO INDAH - Hindaryatiningsih, Nanik; Harjaty, Erny; Safarudin, La Ode; Basri, Asriyani Mulia; Munadi, La Ode Muh. (MAJU : Indonesian Journal of Community Empowerment, 2024)
Baubau, Southeast Sulawesi, moringa leaves are generally only processed into clear vegetable soup which is believed to have medicinal properties, but have not been developed into processed products that are attractive, competitive, and have high economic value. In fact, if this business is managed seriously, it can provide benefits to the community of Bukit Wolio Indah Village, Wolio District, Baubau City. This activity was carried out through the Focus Group Discussion (FGD) method, practice, and mentoring. The results of the activity showed that partners initially had very limited knowledge about the benefits, properties, and how to process moringa leaves. However, after participating in education and direct practice, partners gained knowledge about the benefits and properties of moringa leaves, as well as skills in processing various moringa products, business management, marketing, packaging, and determining selling prices. Based on the evaluation, this local food business management education based on moringa leaves has been utilized by the Majelis Taklim mothers to start a home business that has the potential to increase family income.